2000
DOI: 10.1046/j.1444-2906.2000.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Body lipid deposition in juveniles of red sea bream Pagrus major, yellowtail Seriola quinqueradiata, and Japanese flounder Paralichthys olivaceus

Abstract: SUMMARY: The characteristics of lipid deposition in juveniles of red sea bream Pagrus major, yellowtail Seriola quinqueradiata, and Japanese flounder Paralichthys olivaceus, were investigated by feeding diets with three lipid levels (approximately 11, 16 and 20%). In red sea bream, the viscera contributed 40–50% to the whole body lipid store and deposited 35–39% of dietary lipid intake (body lipid gain/lipid intake : lipid deposition ratio), while the carcass contributed 40% and deposited 30–37%. In yellowtail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
2
9
2
1
Order By: Relevance
“…However, when the diet containing a high crude lipid level (i.e., the CL270 diet) was fed to juvenile kelp grouper, lipid retention significantly decreased. Differences in capacity to store lipid and ability to generate lipidstoring cells and tissues have been reported in several species [28,29]. Thus, our results suggest that the kelp grouper's ability to store lipid is not high.…”
Section: Discussioncontrasting
confidence: 60%
“…However, when the diet containing a high crude lipid level (i.e., the CL270 diet) was fed to juvenile kelp grouper, lipid retention significantly decreased. Differences in capacity to store lipid and ability to generate lipidstoring cells and tissues have been reported in several species [28,29]. Thus, our results suggest that the kelp grouper's ability to store lipid is not high.…”
Section: Discussioncontrasting
confidence: 60%
“…These results are in agreement with that reported by Lee et d~, (2000) who showed a significant decrease from 7% to 16% in weight gain. Almost the same trend was found by Oku and Ogata, (2000) who reported \ 0.5 % to 20% growth rate decrease as well as what has been reported by Alain et al 3 (2003) reporting a reduction of 10% to 20% of growth rate. Also, Watanabe et of.…”
Section: Hematological Parameterssupporting
confidence: 77%
“…This study demonstrated a marked seasonal variation in muscle lipid content of cultured yellowtail, and the results were in agreement with the previous report of Shimizu et al 25 Furthermore, the lipid storage capacity of yellowtail muscle seems to be very high, which presumably is influenced by dietary lipid intake and the physiological state of the fish (maturation and spawning). Recently, Oku and Ogata26 reported that juvenile yellowtail have a large capacity for lipid deposition in the muscle, and the muscle develops its entire lipid storage capacity according to the dietary lipid intake. Crude protein and ash contents varied slightly over the study period, but remained largely constant for most of the samplings.…”
Section: Resultsmentioning
confidence: 99%
“…The stronger correlation ( r = −0.705 to −0.841) observed in this study between muscle lipid content and meat breaking strength than that reported earlier for rainbow trout suggests that cultured yellowtail is more prone to meat tenderness with increasing muscle lipid content. Oku and Ogata26 reported that cultured yellowtail has a large capacity for lipid storage in the carcass. Combining this with the results of the present study, it is obvious that muscle lipid content has a considerable bearing on the meat texture of cultured yellowtail.…”
Section: Resultsmentioning
confidence: 99%